Formation of Students in the Field of Technological Education on the Basis of Innovative Approach - Zokirova Nragiza Akbarjonovna (Periodica Journal, 2022)
This article describes the content of education, the purpose of education, the expected outcome, the correct choice of teaching methods, forms and tools, the development of clear criteria for assessing students' knowledge, skills and abilities in the design of educational processes among teachers and students. the expediency of focusing on implementation and harmonization with each other is highlighted
Keywords: interactive; innovation; map; carpentry